Factors affecting the rapid changes of protein under short-term heat stress - Bingjin Wu; Jianwen Qiao; Xiaoming Wang; Manshuang Liu; Shengbao Xu; Daojie Sun (BMC Genomics, 2021)
Abstract Background Protein content determines the state of cells. The variation in protein abundance is crucial when organisms are in the early stages of heat stress, but the reasons affecting their changes are largely unknown. Results We quantified 47,535 mRNAs and 3742 proteins in the filling grains of wheat in two different thermal environments. The impact of mRNA abundance and sequence features involved in protein translation and degradation on protein expression was evaluated by regression analysis. Transcription, codon usage and amino acid frequency were the main drivers of changes in protein expression under heat stress, and their combined contribution explains 58.2 and 66.4% of the protein variation at 30 and 40 °C (20 °C as control), respectively. Transcription contributes more to alterations in protein content at 40 °C (31%) than at 30 °C (6%). Furthermore, the usage of codon AAG may be closely related to the rapid alteration of proteins under heat stress. The contributions of AAG were 24 and 13% at 30 and 40 °C, respectively. Conclusion In this study, we analyzed the factors affecting the changes in protein expression in the early stage of heat stress and evaluated their influence.